Hidden - Anisa Abdul Latiff (2017)
“Hidden”, a short comedic thriller follows an average tough lady, Renee, who happens to have a clumsy side. As nature calls, she stumbles into a public restroom to relieve herself. However, she lands herself in trouble after she drops her phone into the commode. While trying to retrieve it, she faces an unexpected change of event.